Investing in Maternal Health : Learning from Malaysia and Sri Lanka - Pathmanathan, Indra; Liljestrand, Jerker; Martins, Jo. M.; Rajapaksa, Lalini C.; Lissner, Craig; de Silva, Amala; Selvaraju, Swarna; Singh, Prabha Joginder (Washington, DC: World Bank, 2013)
This study provides the most comprehensive and detailed analysis available on factors behind the decline in maternal mortality in Malaysia and Sri Lanka in the past 50 to 60 years and the magnitude of health system expenditures on maternal health. The main findings are that a modest investment in maternal health services, combined with other poverty reduction measures leads to a fairly rapid decline in the maternal mortality ratio (MMR), defined as the number of maternal deaths per 100,000 live births. The strategies of Malaysia and Sri Lanka changed over time, from an initial emphasis on expanding the provision of services, especially in underserved areas, to increasing utilization and, finally, to emphasizing the improvement of quality. Removing financial barriers to maternal care for clients was an important step in both countries. Professional midwives constitute the backbone of maternal care in Malaysia and Sri Lanka. The MMR reduction in developing countries is feasible with modest public expenditures when appropriate policies are adopted, focused wisely, and adapted incrementally in response to environmental conditions and systems capacity.